The Efficacy of Inactivated Oil Emulsion Newcastle Disease Vaccine - Rahaju, Ernawati (1983)
The preparation of an experimenta1 oi1 emulsion Newcastle disease vaccine is described and its efficacy was evaluated in broiler chickens. A plaque purified clone of Mukteswar strain of Newcastle disease virus designated UPM-AC/2 was used for the preparation of the vaccine. The virus had a titre of 10^11 fifty percent egg infective dose. The vaccine virus was inactivated with betapropiolac tone at a final concentration of 0.1 percent. The vaccine was prepared by mixing the antigen with variable concentration of Arlacel A and Tween 80. Two types of vaccines were prepared, a single oil emulsion and a double oil emulsion vaccine. Both vaccines were evaluated for their stability, viscosity emulsion type, safety and antibody response in chicken. The double emulsion vaccine containing 6% Arlacel A and 1.5% Tween 80 had low viscosity and was stable for at least 6 months at room temperature. The vaccine induced marked antibody response in chickens which were previously vaccinated with lentogenic live Newcastle disease vaccine. The vaccine was also evaluated for its efficacy in broiler chickens which had been previously vaccinated with live Newcastle disease vaccine. Broiler chickens which had been vaccinated when day old with the live Newcastle disease vaccine and revaccinated when 3 weeks and 8 weeks old with the emulsion vaccine were protected when challenged with a viscerotropic velogenic Newcastle disease virus. Between 90 to 100 percent of the vaccinated chickens were resistant to the challenge compared to 100% mortality in the non vaccinated control chickens.